Trichotillomania Treatment Based on Trauma: Case Report - Gorgulu, Serap Akdeniz (Archives of Clinical and Medical Case Reports, 2020)
Trichotillomania is characterized by recurrent pulling out of hair. It is a chronic disorder that causes functional impairment. Although trichotillomania has been known for a long time, no algorithms for its treatment have been created by now. In its etiology, trauma has also been suggested in addition to other factors. In this case study, a trichotillomania patient of 27 years with increasing severity accompanied by a history of trauma is reported. As medical treatment, aripiprazole augmentation was used, and for trauma therapy, EMDR (Eye Movement Desensitization and Reprocessing) was applied. The effects working through the trauma had on the treatment of our case was observed and discussed.